I risultati della politica economica del governo Renzi nei primi due anni - Di Pace, Massimiliano (Argomenti, 2016)
“- austerity = + economic growth” equation has been the focus of Renzi’s Government economic policy, as stated in the Italian Stability Program 2014. This research proves that Italy did not experience such trade-off in the short term. Furthermore, as mainstream literature had demonstrated, as to the negative correlation between high public debt and economic growth, this investigation has collected evidence that the growth of public debt, in absolute terms and in relationship with Gdp, has been accompanied in Italy by economic stagnation. Moreover, data show that this situation is, in the European framework, a phenomenon nearly exclusively specific to Italy.